Paradigma Penelitian Akuntansi dan Keuangan - Sudarma, Made (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This article proposes explores the paradigms that could be used in accounting and financial researches. There are other paradigms beside the positivism, which is the dominating and most currently used paradigm. This article argues that other paradigms, such as post positivism offers a new way of conducting research. It must be noted that each paradigm has its advantages. Quantitative method could be employed in when data is observable and measurable, and when a researcher is testing hypotheses or trying to make generalization. Qualitative method, on the other hand, is more useful when social situation is complex, dynamics and when a researcher decides to understand the situation deeper or to build a new theory.